METODE QAWAID WA TARJAMAH DALAM PEMBELAJARAN QIROAH MENGGUNAKAN KITAB DURUS AL LUGHAH DI MADRASAH ALIYAH AR-ROYYAN PACITAN - Admoko, Fito Andri; Alwi, itsnaini Muslimati (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
The purposes of this study to examine the implementation, strategies, and obstacles in implementing the qawaid wa tarjamah method in learning qiroah using the durus al lughah book at Madrasah Aliyah Islamic Boarding School for the Tahfidzul Qur’an Ar Royyan Pacitan. The qawaid wa tarjamah method is a method that emphasizes understanding grammar to achieve the skills of reading, writing, and translating Arabic texts. The method used is descriptive qualitative approach with data were collected through observation, interviews and documentation. The findings reveal that the qawaid wa tarjamah method, which involves reviewing the studies, practicing the knowledge in daily life, and mentoring by teachers is considered effective in improving student ability in Arabic. Daily conversation, yaumul ilmi, and muhadhoroh also become supporting factors in improving student Arabic language skills. However, several challenges were identified in the implementation of this method, including different student abilities, students forgetting mufrodad, and limited student learning time.